DEVELOPING CONNECTED SPEECH IN PRESCHOOL-AGED CHILDREN BY TEACHING THEM TO COMPOSE STORY: THE EXAMPLE OF UZBEKISTAN - Imikhanova Nodira Saidburkhon kizi (Journals Park Publishing, 2026)
The article analyzes the practice of developing coherent speech in preschool children by teaching them to compose stories in the conditions of Uzbekistan. The results of the study show that creating stories based on pictures and fairy tales, dramatic games and interactive exercises significantly increase children's vocabulary, grammatical structure and logical consistency. The article provides methodological recommendations for educators.
Keywords: Preschool age, coherent speech, composing a story, speech development, pedagogical practice, Uzbekistan.